Sequence analysis of the Toll-like receptor 2 gene of old world camels - Shyam S. Dahiya; Govindasamy Nagarajan; Vijay K. Bharti; Shelesh K. Swami; Sharat C. Mehta; Fateh C. Tuteja; Shirish D. Narnaware; NitinV. Patil (Journal of Advanced Research, 2014)
The Toll-like receptor 2 (TLR2) gene of old world camels (Camelus dromedarius and Camelus bactrianus) was cloned and sequenced. The TLR2 gene of the dromedary camel had the highest nucleotide and amino acid identity with pig, i.e., 66.8% and 59.6%, respectively. Similarly, the TLR2 gene of the Bactrian camel also had the highest nucleotide and amino acid identity with pig, i.e., 85.7% and 81.4%, respectively. Dromedary and Bactrian camels shared 77.9% nucleotide and 73.6% amino acid identity with each other. Interestingly, the amidation motif is present in camel (Dromedary and Bactrian) TLR2 only, and the TIR domain is absent in Dromedary camel TLR2. This is the first report of the TLR2 gene sequence of Dromedary and Bactrian camels.